(untitled) (Bulletin of criminological association of Ukraine, 2023)
The article emphasizes that bodies with greater institutional independence demonstrate better effectiveness in investigating offenses and successfully bringing guilty persons to justice than bodies under direct governmental control and management. The key differences between the category "anti-corruption entities subject to the highest political leadership of the state" and the category "independent anti-corruption entities" are highlighted. The author’s approach to the classification of domestic anti-corruption entities according to the level of their efficiency and transparency is outlined. In particular, this criterion covers the evaluation of the success of detection, investigation and termination of corruption acts. It was established that Ukrainian independent anti-corruption bodies, such as NABU and SAP, are leaders in this indicator and demonstrate better performance than other law enforcement agencies. Attention was focused on the need to implement complex reforms aimed at strengthening the legal system, increasing transparency in power structures, and creating conditions for active public participation. The active participation of civil society in combating corruption was noted. Public organizations, journalists and activists highlight corruption schemes and expose violations of the law, providing valuable information to law enforcement officers. A general analysis of the activities of the National Agency for the Prevention of Corruption (NABU), the Specialized Anti-Corruption Prosecutor’s Office (SAP), the National Agency for the Prevention of Corruption (NAZK) and the High Anti-Corruption Court as components of the anti-corruption system was carried out, the characteristic features of which include the distribution of spheres of responsibility, independence from the authorities and the presence of a special status, support of international partners, promotion of democracy in Ukraine, ensuring the right of citizens to fair conditions for business and equal opportunities of access to the spheres of education and science, health care, culture and leisure of citizens, a significant level of transparency and openness.